2015
DOI: 10.1021/acs.biochem.5b01016
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces wadayamensis MppP Is a Pyridoxal 5′-Phosphate-Dependent l-Arginine α-Deaminase, γ-Hydroxylase in the Enduracididine Biosynthetic Pathway

Abstract: L-Enduracididine (L-End) is a nonproteinogenic amino acid found in a number of bioactive peptides, including the antibiotics teixobactin, enduracidin, and mannopeptimycin. The potent activity of these compounds against antibiotic-resistant pathogens like MRSA and their novel mode of action have garnered considerable interest for the development of these peptides into clinically relevant antibiotics. This goal has been hampered, at least in part, by the fact that L-End is difficult to synthesize and not current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 59 publications
5
57
0
1
Order By: Relevance
“…The amino acid l ‐arginine has emerged as a common substrate for sequence‐related oxygen‐dependent PLP enzymes from Streptomyces bacteria. These enzymes include Ind4 from the indolmycin biosynthetic pathway [71,72], MppP from enduracididine biosynthesis [73,74], and RohP from the azomycin biosynthetic pathway [75,76]. Indolmycin, enduracididine, and azomycin each contain arginine‐derived heterocycles, for which Ind4, MppP, and RohP are essential upstream enzymes toward the biosynthesis of each heterocycle.…”
Section: L‐arginine Oxidases Linked To Heterocycle Biosynthesismentioning
confidence: 99%
“…The amino acid l ‐arginine has emerged as a common substrate for sequence‐related oxygen‐dependent PLP enzymes from Streptomyces bacteria. These enzymes include Ind4 from the indolmycin biosynthetic pathway [71,72], MppP from enduracididine biosynthesis [73,74], and RohP from the azomycin biosynthetic pathway [75,76]. Indolmycin, enduracididine, and azomycin each contain arginine‐derived heterocycles, for which Ind4, MppP, and RohP are essential upstream enzymes toward the biosynthesis of each heterocycle.…”
Section: L‐arginine Oxidases Linked To Heterocycle Biosynthesismentioning
confidence: 99%
“…[18] Biochemical ands tructural studies showed that MppP is aP LP-dependent hydroxylase, which catalyzes the conversion of l-Arg and dioxygen to produce 2-oxo-4-hydroxy-5-guanidinovaleric acid (1)( Figure 5). [19] MppR shares ah igh degree of structurals imilarity with acetoacetate decarboxylase, which converts 1 to 3-[(4R)-2-iminoimidazolidin-4-yl]-2-oxopropanoic acid (2), the ketone form of l-End. [20] The PLP-dependenta minotransferase MppQ then catalyzes the reductivea mination of 2 to produce l-End ( Figure 5).…”
Section: Biosynthesis Of Teixobactinmentioning
confidence: 99%
“…Strukturell noch ungewöhnlicher sind die cyclischen Arg‐Analoga Enduracididin (End), bekannt von Mannopeptimycin, sowie das Capreomycidin (Cap), ein Bestandteil von Peptiden der Tuberactinomycin‐Gruppe wie des Viomycins. Für End wie auch für Cap (Schema a) wird Arg als Ursprung vorgeschlagen. Einiges deutet darauf hin, dass β‐Cyanalanin (Cya) ATP‐abhängig nach einem NRPS‐gebundenen Mechanismus durch Dehydratisierung aus Asn synthetisiert wird .…”
Section: Die Aminosäurebausteine – Grundlage Für Strukturelle Diversunclassified